Clinical Profile and Treatment Outcome of Chordoma: A Tertiary Care Experience in North India - Tali, Tavseef Ahmad; Amin, Fiza; Dar, Javaid Ahmad; Sofi, Mushtaq Ahmad; Dar, Nazir Ahmad (Indonesian Journal of Cancer Chemoprevention, 2022)
Chordoma is a slow growing cancer of tissue found inside the spine. Chordoma can happen anywhere along the spine. It is most often found near the tailbone (called a sacral tumor) or where the spine meets the skull (called a clival tumor). Chordoma is also called notochordal sarcoma. The main objective of this study was to determine the clinical profile and treatment outcome of chordoma patients. All the patients were diagnosed using radiological imaging and biopsy. The site of origin of chordoma was the sacrum in seventeen (71%) patients, the spine in six (25%) patients, and the skull base in one (4%) patient. 21 (88%) of the twenty-four patients received primary surgery. These 21 patients then received adjuvant radiation therapy using the intensity modulated radiation therapy (IMRT) strategy, with radiation dose ranging from 70Gy to 74Gy. Three patients (12%) did not undergo surgery; two had low performance status and received only radiotherapy; the third with the disease at the base of the skull was unresectable; this patient received radiotherapy first, then imatinib. Compared to individuals who get radiation alone, the addition of adjuvant radiation therapy to surgery in chordoma patients enhances overall survival.Keywords: chordoma, radiotherapy, targeted therapy.